2008
DOI: 10.1007/s00044-007-9080-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of new compounds from seeds of Nigella sativa

Abstract: Two new triterpenoids were isolated from the n-hexane extract of seeds of Nigella sativa Linn. and identified as cycloart-23-methyl-7,20,22-triene-3b, 30-diol (1) and cycloart-3-one-7,22-diene-24-ol (2). In addition, two aliphatic compounds and two known sugars were isolated from alcohol extract, and identified as 4-hydroxy undecyl nonanoate (3), 14,20-dimethyl heptacosanol (4), maltose (5), and sucrose (6). They were characterized on the basis of spectral analysis and by comparing literature data. Extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…It has been shown that the biological properties of the essential oils are directly associated with the chemical composition, which varies depending on the origin (Bourgou et al, 2010). Several of the pharmacologically interesting substances have also been isolated from Nigella seeds including isoquinoline and indazole alkaloids (Atta, 2003;Atta-ur-Rahman et al, 1995), saponins (Mehta et al, 2009), cycloartenols (Mehta et al, 2008), and flavonoid glycosides (Merfort et al, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that the biological properties of the essential oils are directly associated with the chemical composition, which varies depending on the origin (Bourgou et al, 2010). Several of the pharmacologically interesting substances have also been isolated from Nigella seeds including isoquinoline and indazole alkaloids (Atta, 2003;Atta-ur-Rahman et al, 1995), saponins (Mehta et al, 2009), cycloartenols (Mehta et al, 2008), and flavonoid glycosides (Merfort et al, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…While N. sativa and R. rosea extracts did not inhibit IBV, many of their phytochemicals are thought to be antiviral. For example, N. sativa seed extracts predominantly contain saponins, glycosides, terpenoids and alkaloids [38,[63][64][65][66][67], many of which are similar to known antiviral chemicals [38][39][40]68]. On the other hand, R. rosea root extracts consist of many kaempferol, herbacetin, dihydromyricetin, and myricetin derivatives [32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, N. sativa seed extracts predominantly contain saponins, glycosides, terpenoids and alkaloids [38,[63][64][65][66][67], many of which are similar to known antiviral chemicals [38][39][40]68]. On the other hand, R. rosea root extracts consist of many kaempferol, herbacetin, dihydromyricetin, and myricetin derivatives [32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of murine cytomegalovirus infection and hepatitis C infection lend support to the plant's antiviral potential in vivo, as well [36,37]. Additionally, N. sativa compound extracts, especially its saponins, alkaloids, and flavonols, show similarities with known antiviral chemicals [38][39][40]. Finally, S. nigra extract has successfully inhibited influenza A and B viruses in vitro and in vivo [41].…”
Section: Introductionmentioning
confidence: 91%